Assessment on knowledge, attitude and practices of food and nutrition labeling usage among adult in kota bharu, Kelantan - Zakaria, Nur Izzul Husna (Universiti Sains Malaysia, 2016)
Food and nutrition labeling contain a lot of information about the food and nutrition which are available on most of food packages. Food and nutrition labeling is one of the tools which play the vital roles in guided the consumers in choosing the healthy foods. The purpose of this study was to assess the knowledge, attitudes and practices on usage of food and nutrition labeling among adult consumers in Kota Bharu, Kelantan. Socio-demographic characteristics such as age, gender, marital status, education level, occupation and body mass index (BMI) also had been assessed to determine the relationship with the usage of food and nutrition labeling. 164 participants were conveniently approached and willing to answer the questionnaire of this study. Almost all of the adults consumers (96.3%) of hypermarket, supermarket and minimarket were tend to read food label information. While finding in this study showed that only 54.9% of adult consumers tend to read nutrition labeling. In this study also found 59.1% of adult consumers understand well on the terms, the important and the role of some of nutrition information on their daily practices and to their health. Besides, only a few of food label information showed the significant association with the socio-demographic characteristics (p<0.005) and gender as well as occupation showed the significant different to the mean of important nutrition information (p<0.05). Thus, nutrition literacy and knowledge should be improve in order to ensure adult consumers can use and interpret wisely the food and nutrition information provided in choosing healthy food.